Feature Writing of Ahmad Bashir - Dr. Riaz Ahmad Riaz; Dr. Farah Abid; Dr. Nadia Anjum (Zaban-o-Adab, 2024)
Ahmad Bashir was a renowned journalist and a literary icon of Urdu. He wrote essays / articles and columns equally in English and Urdu. Among the various of his journalistic and literary facets, sketch-writing, novel-writing and editorial-writing are worth-mentioning. He got education in film-making from America, and then started film-making and direction in Pakistan. He produced few documentaries, and made the first and the last to date belly film of Pakistan "Chirree Kahaani" that achieved an award in belly film festival of Iran. He chose journalism for making his livelihood, and learnt journalism from Charagh Hassan Hassrat in the daily "Amroz". He was called the founder of Urdu feature-writing. He wrote his debut feature on Gaamma Pehalwaan. After the daily "Amroz", he started writing for the weekly "Qandeel". He never sticked long to a newspaper owing to his truthfulness and ideological thoughts. He exhibited his writing power, along with editorial writing, in both English and Urdu journals and newspapers like: "Chataan", "Lail-o-Nahaar", "Nawa-e-Waqt", "Jang", "Musawaat", "Friday Times", "The Muslim", "The Star", "The News" and "Frontier Post". His last writing, featuring the journalistic; political; analytical and ideological characteristics, continued to publish in the monthly "Naya Zamaana" from Lahore. His style held truthfulness and candidness. He had to write uder different false names due to the atrocities of the government. He adopted the names of Bhulley Shah, Shah Anyat and Ahmad Khan Kharal for this purpose. He never let the journalistic and literary values fall a prey to worldly strategies and impurities. He was a staunch socialist and flag-bearer of social justice.